(untitled) (Research, Society and Development, 2021)
Introduction: Autism Spectrum Disorder (ASD) is characterized by clinically relevant and permanent deficits in social communication and social interactions. Limitations of verbal and non-verbal communication, lack of social reciprocity, friendship relationships compromised for the developmental stage, restricted and repetitive behaviors, being these stereotyped motor and verbal behaviors or unusual sensory ones, exaggerated adherence to ritualized routines and patterns, summarized interests and intense. Objective: To analyze the effects of drug and non-drug treatment of patients with autism spectrum disorder (ASD) on the vision of caregivers. Methods: Field research, descriptive and quantitative, carried out with 59 caregivers from the Sertão da Paraíba and Cariri regions in Ceará. Data collection was carried out with an online questionnaire prepared on Google Forms, in which caregivers of children with ASD received the link through instant messaging groups (WhatsApp) in the regions mentioned. For data analysis, descriptive tests of measures of central tendency and dispersion were used, as well as the Binary Logistic Regression test (enter method). Results: The average age of the children was 6.25 years, most were male (94.9%), diagnosed with closed ASD (89.8%) and started attending school between 0-3 years old. (76.3%). Among the medications, the one that was most used was rispiridone (40.7%). Most reported that medications have side effects (62.5%), including increased appetite (28.8%). In addition, 88.1% of caregivers reported that patients used non-drug treatment, considering it as the one that provides better quality of life (76.3%). There were statistically significant associations between drug treatment, aggressive behavior (c2 (1) = 6.133, p< 0.013, f = -0.322), hyperactivity (c2 (1) = 8.854, p<0.003, f = -0.387) and quality of sleep (c2 (1) = 27,717, p< 0.0001, f = -0.345). In addition, non-drug treatment was associated with sensory-integral occupational therapy (c2 (1) = 3.622, p<0.057, f = -0.248). Conclusion: Non-drug treatment was appointed as the most responsive, providing improvements in core symptoms, with improved quality of life, in addition to not causing side effects, while drug therapy is related to the treatment of specific symptoms, and may bring Side effects.